2016
DOI: 10.1017/s1751731116000471
|View full text |Cite
|
Sign up to set email alerts
|

Impact of parity on bone metabolism throughout the reproductive cycle in sows

Abstract: Bone metabolism fluctuates throughout the reproductive cycle of sows to enable foetal growth and milk production. Although increased bone mineralisation is conceivable in sows during reproduction, a study of mineralisation in function of parity has not been performed. This study evaluated the fluctuations of markers for bone metabolism in primiparous and multiparous sows throughout a reproductive cycle. The experiment included ten multiparous and five primiparous commercial hybrid sows from one herd. The sows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…Earlier studies in ruminants and sows suggested this tissue mobilisation for nutrients from bone around parturition (Liesegang et al, 2000;van Riet et al, 2016) and in this study as the (non-significant) TA B L E 2 Bodyweight (BW) (mean ± SEM) and back fat thickness (BF) (mean ± SEM) throughout the reproduction cycle of sows The ratio of 3-hydroxybutyrylcarnitine to acetylcarnitine was studied as an estimator for the less efficient energy production through formation of ketone bodies (Livesey & Elia, 2004;van der Meulen et al, 1997;Theil, Olesen, Flummer, Sorensen, & Kristensen, 2013). Acetylcarnitine and 3-hydroxybutyrylcarnitine mirror the mitochondrial acetyl-coenzyme A and β-hydroxybutyryl coenzyme A pool, respectively, and its ratio reflects the relative scarcity of metabolites available for the citric acid (TCA) cycle (Verbrugghe et al, 2010).…”
Section: Gestationmentioning
confidence: 98%
“…Earlier studies in ruminants and sows suggested this tissue mobilisation for nutrients from bone around parturition (Liesegang et al, 2000;van Riet et al, 2016) and in this study as the (non-significant) TA B L E 2 Bodyweight (BW) (mean ± SEM) and back fat thickness (BF) (mean ± SEM) throughout the reproduction cycle of sows The ratio of 3-hydroxybutyrylcarnitine to acetylcarnitine was studied as an estimator for the less efficient energy production through formation of ketone bodies (Livesey & Elia, 2004;van der Meulen et al, 1997;Theil, Olesen, Flummer, Sorensen, & Kristensen, 2013). Acetylcarnitine and 3-hydroxybutyrylcarnitine mirror the mitochondrial acetyl-coenzyme A and β-hydroxybutyryl coenzyme A pool, respectively, and its ratio reflects the relative scarcity of metabolites available for the citric acid (TCA) cycle (Verbrugghe et al, 2010).…”
Section: Gestationmentioning
confidence: 98%
“…Bone markers (CTX-I, OC) showed significant differences between MMA and healthy sows. It is well known that markers for bone resorption increase at the end of gestation due to the rapid growth of the foetuses and at the beginning of lactation in several species including swine (Liesegang et al, 2005;van Riet et al, 2016), ruminants (Liesegang et al, 2000;Liesegang, Risteli, & Wanner, 2007), equine (Filipović, Stojević, Prvanović, & Tuček, 2010) and humans (Kaur et al, 2003;Naylor, Iqbal, Fledelius, Fraser, & Eastell, 2000). In this study, MMA-affected sows showed a catabolic bone metabolism, which can be linked to higher serum concentrations of pro-inflammatory cytokines.…”
Section: Bone Markers Minerals Tnfα Il-6 and Haptoglobin In Serummentioning
confidence: 66%
“…Calcium (Ca) is released simultaneously with P, and the bone thus becomes unstable (Liesegang, Loch, Bürgi, & Risteli, 2005). In sows, markers for bone formation decrease at start of lactation and markers for bone resorption increase in late gestation and rise significantly after farrowing due to the start of lactation (van Riet et al, 2016). At the same time, markers for bone resorption are increasing, and osteocalcin (OC), a marker for bone formation, decreases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cette mobilisation est très rapide au regard de la vitesse de renouvellement de l'os en situation d'équilibre qui est évaluée à 10 % par an en moyenne chez l'Homme adulte (Kenkre et Bassett, 2018) avec des différences importantes selon le type d'os (os cortical : 4 % vs. os spongieux : 25 % ; Lefèvre, 2016). La résorption de l'os s'accentue pendant la lactation (van Riet et al, 2016), dès lors que la capacité maximale d'ingestion de la truie est atteinte plus tôt que le pic de lactation. Quand elle est provoquée par un déficit en calcium ou en phosphore, il s'ensuit inexorablement la libération de l'autre élément.…”
Section: Réserve Et Mobilisation Du Caunclassified